Molecular Characterization of Moraxella Catarrhalis and it’s Antibiotics Susceptibility Patterns from Different Respiratory Tract Infection Patient’s Clinical Samples - Jha, Brajesh Kumar; Upadhyay, Hari Prasad; Mahadevamurthy, S; Sudisha, J (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Moraxella catarrhalis is a gram negative, oxidase positive, cocci mainly causing upper and lower respiratory tract infections. The RND family efflux pumps lead to multidrug resistance in most of the gram negative bacteria. One of the well- known pumps in M. catarrhalis is arcAB and oprM system. The objective of this study was to investigate the antibiotic resistance in M. catarrhalis and to determine its resistance dependence on the efflux pump. Methods In this study, 283 different respiratory tract infection samples processed out of that 73 were confirmed by biotyping and molecular characterization as a M. catarrhalis. The antibiotic susceptibility tests were performed by disc diffusion method according to CLSI. Molecular characterization for multidrug resistance isolates was also done along with genes responsible for efflux pumps. PCR was done M. catarrhalis and acrAB and oprM genes. The factor for association of efflux pump with antibiotic resistance was investigated using phenylalanine argine β-naphthylamide. Results The antibiotics susceptibility result showed 12 out of 73 isolates were MDR, selectively taken for PCR using 16SrRNA specific primer. The MDR isolates were further confirmed by PCR. The amplification results of acra, acrb and oprm genes for the M. catarrhalis having multidrug resistance genes by PCR band size products seen on 2% agrose gel. The highest resistance towards the drugs viz penicillin, ampicillin, amoxicillin, amoxiclave, cotrimoxazole, cefazolin, cefuroxime, ceftrixone and cefepime were seen in M. catarrhalis. Conclusions The result showed that Moraxella catarrhalis is one of the major causes for respiratory tract infection. The drug resistance in this species is increasing day by day. The 90% of isolates have acrAB and oprM genes for efflux pump responsible for multiple drug resistance. The efflux pump inhibitor has important clinical significance for the proper treatment.